2000
DOI: 10.1046/j.1464-410x.2000.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

The actions of metabolic inhibition on human detrusor smooth muscle contractility from stable and unstable bladders

Abstract: Objectives To determine the important cellular site(s) of action of a brief exposure to NaCN (chosen to reduce mitochondrial respiration and hence mimic cellular hypoxia) on the mechanical properties and regulation of intracellular [Ca 2+ (15)% in the two groups; the reduction in the unstable was signi®cantly less than in the stable group. NaCN similarly reduced the response to 10 mmol/L caffeine, but had no effect on the KCl-induced contraction. NaCN signi®cantly increased the resting sarcoplasmic [Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Moreover, caffeine increases intracellular levels of cAMP via its phosphodiesterase activity; cAMP causes muscle relaxation, and might directly influence the [Ca 2+ ] i ‐tension relationship. If so, the latter would play a major role [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, caffeine increases intracellular levels of cAMP via its phosphodiesterase activity; cAMP causes muscle relaxation, and might directly influence the [Ca 2+ ] i ‐tension relationship. If so, the latter would play a major role [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…A separate study using a mouse model found that oral caffeine administration resulted in detrusor overactivity and increased bladder sensory signaling . Further studies found similar effects on the detrusor muscle in humans . However, the direct effects of caffeine, its delivery into cells, and its mechanisms remain unestablished.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro caffeine appears to have an excitatory effect on the human detrusor smooth muscle. 7 A single study of the effects of caffeine ingestion on bladder contractility in diabetic rats showed that chronic oral administration of caffeine or coffee increased the contractility of isolated detrusor smooth muscle strips. 8 The group found an increased cyclic adenosine monophosphate concentration in the bladder of caffeine treated animals and postulated that this was the mechanism underlying the observed effect.…”
mentioning
confidence: 99%